Incidental diagnosis of thoracic ganglioneuroblastoma in a 3 years old female with wheezing - Lucaccioni, L.; Bigi, E.; Garcinuno et al., C.C. (Acta Biomedica Atenei Parmensis, 2012)
Ganglioneuroblastoma (GNB) is a cancer of the peripheral sympathetic nervous system and represents the 30% of cases of Neuroblastoma.When originates from thoracic ganglia it may appear very late, with severe symptoms like respiratory distress or neurological dysfunctions.We present an incidental diagnosis of thoracic GNB, discovered by a chest radiography during a recurrent wheezing unresponsive to bronchodilators. The early diagnosis allowed a precocious treatment probably improving the outcome.